2021
DOI: 10.3390/ijms22052672
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Superoxide on At-Level Spinal Cord Injury Pain in Rats

Abstract: In the present study, we examined superoxide-mediated excitatory nociceptive transmission on at-level neuropathic pain following spinal thoracic 10 contusion injury (SCI) in male Sprague Dawley rats. Methods: Mechanical sensitivity at body trunk, neuronal firing activity, and expression of superoxide marker/ionotropic glutamate receptors (iGluRs)/CamKII were measured in the T7/8 dorsal horn, respectively. Results: Topical treatment of superoxide donor t-BOOH (0.4 mg/kg) increased neuronal firing rates and pCam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Many previous studies have shown that ROS are involved in the hyperalgesia in NMDA-induced pain model [ 69 ] or capsaicin-induced pain model [ 70 ] at the spinal cord level, or in visceral pain model [ 71 ] at amygdala level, or in cisplatin-evoked [ 72 ] or CCI -evoked pain model [ 73 ] at DRG level, or in hypoxia/reoxygenation-evoked acute hyperalgesia [ 74 ] at microglia, or in spinal nerve ligation (SNL)-induced NP model at astrocytes [ 75 ]. Moreover, treatment of ROS donor t-BOOH could induce allodynia [ 76 ]. Previously Kallenborn-Gerhardt W [ 77 ] et al and Grace PM et al [ 78 ] have reviewed how the ROS is generated after NP enhances neuroexcitability in pain pathways and the potential therapeutic strategies for normalizing ROS.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have shown that ROS are involved in the hyperalgesia in NMDA-induced pain model [ 69 ] or capsaicin-induced pain model [ 70 ] at the spinal cord level, or in visceral pain model [ 71 ] at amygdala level, or in cisplatin-evoked [ 72 ] or CCI -evoked pain model [ 73 ] at DRG level, or in hypoxia/reoxygenation-evoked acute hyperalgesia [ 74 ] at microglia, or in spinal nerve ligation (SNL)-induced NP model at astrocytes [ 75 ]. Moreover, treatment of ROS donor t-BOOH could induce allodynia [ 76 ]. Previously Kallenborn-Gerhardt W [ 77 ] et al and Grace PM et al [ 78 ] have reviewed how the ROS is generated after NP enhances neuroexcitability in pain pathways and the potential therapeutic strategies for normalizing ROS.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Murugappan et al [12] revealed that blocking afferent signals with a tetrodotoxin (TTX) reduced mechanical allodynia and rescued decision-making deficits, but the TTX could not reduce the allodynia and improve decision-making deficits at a later phase, suggesting that early pain relief is more important for functional recovery from pain-related cognitive deficits. Using a CNS model of neuropathic pain, Lee et al [13] observed that the level of superoxide marker dihydroethidium significantly increased in rats with spinal cord injuries compared to the sham rats. Furthermore, intrathecal administration of superoxide scavenger 4-hydroxy-2,2,6,6-tetramethylpiperidinyl-1-oxyl (TEMPOL) and non-specific reactive oxygen species (ROS) scavenger N-tert-butyl-α-phenylnitrone (PBN) decreased firing rates in the spinal cord injury (SCI) group.…”
mentioning
confidence: 99%